Economy And Moral Education In Early Republican Period Of Turkey - Kumbal, Serhat; Temel, Mehmet (European Scientific Journal, ESJ, 2016)
In the early Republican period of Turkey, governments placed significant importance to education council meetings in order to structure educational policies. While these councils gathered as a consulting unit, necessary reports on the subjects determined by governments were prepared and submitted back to governments as suggestions. Whereas the first of these councils was held in 1939; the second one was held in Ankara under the title of “the Second Educational Council (SEC)” to discuss issues on morals, language and history in the period of February 15th-21st, 1943. In the present study, reasons and purposes of the moral education taken into consideration during the SEC were tried to be comprehended. To that end, four basic principles considered within the scope of the moral context in the council were tried to be structured on the economical context of the early Republican period. As a result of the study, it was concluded that some behavior and attitude types requested by leaders of the mentioned era and institutional spurts taken into the agenda along the economic targets determined during the construction of modern Turkey were taken into consideration under morality concept in the SEC in 1943.